Välfärdsmärkning : åsikter bland svenska grisproducenter om en produktmärkning för god djurvälfärd - Ögren Kull, Sonia (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
Authors, scientists and politicians all say the same thing – the society is moving towards a future where the consumers voice their concerns regarding animal welfare and interest in animal friendly products. According to the research, the consumers are willing to pay extra to know that the meat they buy comes from animals that have lived happy lives. The best way to market this is by clear and simple labeling. Organic production requires approximately twice the amount of farmable land to grow the same amount of grains as conventional and some scientists mean that organic is not the given solution for a sustainable agriculture. For a conventional pig producer to become organic is not only expensive, but also very time-consuming because of the requirement to turn the entire land to ecological and to do so during a qualifying period. To meet the demands for a sustainable agriculture and the consumer’s wishes for good animal welfare a new kind of label is required, a welfare label. The aim of this study was to study the opinions among pig producers in Sweden about an animal welfare label and if it would be something they would be interested in. Therefore a survey was sent out by e-mail to all Sweden’s pig holders registered with the Swedish Board of Agriculture. Of 2140 recipients, 385 pig holders responded. 309 of these responds were complete and used for data analysis. The study showed that 71 % of the 309 responders were interested of joining the label and 29 % would do so even if it did not result in an increased profitability. The type of pig producers that were most interested were those that kept both sows with piglets and fattening pigs integrated (P = 0,0013). In Götaland, 76 % of the respondents were interested. The respondents also scored different components of a pig’s welfare and how well they thought they achieved the same components in their own production. Healthy animals and low use of antibiotics were thought to be most important for pig welfare and producers also thought that their own production best achieved these two components, together with lying comfort. Outdoor access was thought to be the least important component and this is also what the producers considered they less well fulfilled in their own production. Of 309 respondents, 103 answered that it was not needed in or relevant for their kind of production. More research is needed to create a successful labeling system but this study could be used as a base for creating such a system. The producers clearly state that they would be interested to join the label.